The effects of target distance on kinematic sequence of the short game in male collegiate golfers - McGuire, T. G.; Picard, C. T.; Ward, R. M.; Smith, D. L.; Kwon, Y. H.; Walsh, M. S. (Sports Biomechanics, 2024)
Golf is an international sport that has become increasingly more popular in recent times. Previous literature has shown that golf approach shots are crucial to the success of elite golfers. However, there is no known publication investigating distances less than 100 yards, known as the short game. The primary purpose of this study was to collect comprehensive data on 3D biomechanical variables of the short game at four target distances in college-aged, male golfers. Participants were instructed to hit five successful shots at each target distance: 30 yards, 50 yards, 70 yards and full swing (maximal distance) yardage. A motion capture system recorded kinematic and temporal parameters of golfer movement, additional to a golf simulator that collected ball carry distance of each shot. Distance did have a significant (p = 0.05) effect on swing phase timing, angular velocities and motion sequencing. Movement sequencing within the short game displayed irregular patterns across all distances and phases, with a partial proximal-to-distal pattern (pelvis - shoulder girdle - arms - club) at best. The findings of this study show that the short game swing did present its own unique motion patterns that will require practice as its own skill.